Unity in Diversity: Examining Religious Moderation across Religions in Indonesia - Maulana, Muhamad; Alifia Putri, Nabila Nindya; Fahira, Zihan (Jurnal Dialog, 2024)
Indonesia's rich religious diversity, epitomized by the concept of "Unity in Diversity," presents both opportunities and challenges. This study delved into religious moderation across Indonesia's six recognized religions, Islam, Christianity (Catholic and Protestant), Hinduism, Buddhism, and, Confucianism, defining it as a commitment to tolerance, inclusivity, and critical thought within religious contexts. In addition to these six religions, Indonesia is unique in recognizing the existence of diverse indigenous beliefs according to different tribes and cultures. Through a literature review, the study revealed that religious moderation varies across different faith communities, yet remains crucial for fostering peace and harmonious coexistence. Interfaith initiatives, religious institutions, and education were identified as key factors in promoting religious moderation. The study concludes that embracing the diverse expressions of religious moderation is essential for building a more inclusive and harmonious Indonesia, where “Bhinneka Tunggal Ika” transcends rhetoric to become a vibrant reality.